The effect of training attributes and the moderating role of changed behaviour on employee performance: an examination in the context of Malaysian hotels / Fadzilah Mohd Shariff - Mohd Shariff, Fadzilah (2013)
Research indicates that more than 80% of the knowledge and skills gained in training programs is not applied in the workplace, but there is growing body of evidence that recognizes managerial involvement as a primary factor in improving training transfer. Individual characteristics and work environment variables have been emphasized by research as important in the transfer of training, but it is surprising that little research has addressed the issue of the employees’ own individual characteristics and work environment variables as being significant in their ability to transfer their knowledge and skills gained from training back to the job. The purpose of the study is to examine the relationship among selected trainee characteristics variables and work environment variables in the process of behavioural change and effect on employee performance in the Malaysian hospitality industry. The two influential factors that emerged from the various learning transfer models were individual characteristics (e.g., motivation) and work environment (e.g., supervisor support, co-worker support, and the opportunity-to-use the available resources). The hypotheses and supporting logic for linkages between the variables are drawn from several research foundation and theories. The proposed hypotheses were tested with data collected from frontline restaurant service employees working in four and five star rating hotels in Kelang Valley, Malaysia. Confirmatory factor analysis (CFA) was utilized to assess the measurement model, and path analysis with structural equation modelling (SEM) was employed to test the proposed hypotheses.The results of the study showed that the proposed individual characteristics and work environment variables have a significant effect on frontline employees’ performance. Employees’ motivation and employees’ performance received strong support in a significant relationship ((3: 0.778, t: 4.510, p<0.001). The relationship between co-worker support and employees’ job performance showed a significant positive relationship, in which the strength of relationships is, P: 0.181, and a /-value of 2.462. Changed behaviour was found to significantly moderate the relationship between frontline employees’ motivation, opportunity-to-use, co-worker support and employees’ job performance. A difference in chi-squared values between the models (0.224, 1,/K0.001; 2.920, 1, pO.OOl; 11.093, 1, /?<0.01) showed that changed behaviour had a moderating effect on employees’ job performance relationship. However, supervisors’ support and opportunity to use the available resources were found to be not a significant determinant of employees’ job performance. The findings of this study have contributed to the body of knowledge by adding new empirical evidence to the direct and indirect relationship between employees’ motivation, work environment variables, changed behaviour and frontline employees’ performance. In relation to managerial implications, the findings would be able to assist Human Resources Managers in decision making, particularly in selecting, recruiting and managing frontline employees in the hotel industry. For training, stakeholders should consider learning as a process rather than a one-time classroom event. Following through on learning activities accelerates the transfer of learning into changed behaviours on the job by ensuring that learning is meaningful, continual, job related and timely. Future study should continue to explore the current study’s variables with a more diversified population in various settings